Dissociation in Effective Treatment and Behavioral Phenotype Between Stress-Enhanced Fear Learning and Learned Helplessness - Conoscenti, Michael A.; Fanselow, Michael S. (Frontiers in Behavioral Neuroscience, 2019)
Post-traumatic stress disorder (PTSD) is a debilitating disease with relatively high lifetime prevalence. It is marked by a high diversity of symptoms and comorbidity with other psychiatric disease. Furthermore, PTSD has a high level of origin and symptom heterogeneity within the population. These characteristics taken together make it one of the most challenging diseases to effectively model in animals. However, with relatively little headway made in developing effective disease interventions, PTSD remains as a high priority target for animal model study. Learned Helplessness (LH) is a procedure classically used to model depression, but has in recent years transitioned to use as a model of PTSD. Animals in this procedure receive 100 inescapable and unpredictable tailshocks or simple restraint without shock. The following day, the animals are tested in a shuttle box, where inescapably-shocked subjects exhibit exaggerated fear and profound deficit in escape performance. Stress-enhanced fear learning (SEFL) also uses an acute (single session) stressor for modeling PTSD in rodents. The SEFL procedure begins with exposure to 15 footshocks or simple context exposure without shock. Animals that initially received the 15 footshocks exhibit future enhanced fear learning. In this review, we will compare the behavior, physiology, and interventions of these two animal models of PTSD. Despite considerable similarity (a single session containing inescapable and uncontrollable shock) the two procedures produce a very divergent set of behavioral consequences.